Analisis Faktor Pengalaman, Pemasaran, dan FOMO dalam Membentuk Keputusan Kunjungan Ulang Turis Domestik ke Jatiluwih, Tabanan - Susanti, Gusti Ayu Komang Viona Ary; Sari, Putu Ratna Juwita; Martini, Ida Ayu Oka; Parasari, Nyoman Sri Manik (Economic Reviews Journal, 2025)
This study aims to determine the influence of tourist experience, promotion, fear of missing out partially and simultaneously on revisit intention. The sample in this study were domestic tourists, had visited Jatiluwih Tabanan, aged at least 17 years, had understood in using social media as many as 152 people. Data analysis techniques used Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Determination Coefficient Test, F Test and t Test. From the results of the study, the results of tourist experience had a positive and significant effect on revisit intention, promotion had a positive and significant effect on revisit intention, fear of missing out had a positive and significant effect on revisit intention and tourist experience, promotion and fear of missing out had a significant effect on revisit intention. The magnitude of the influence of independent variables on revisit intention was 55.6%. The researcher's suggestion is that the management of the Jatiluwih Tabanan tourist attraction should introduce local culture to tourists through Jatiluwih's specialties and traditional Jatiluwih agriculture. In conducting promotions, they should always provide interesting and complete information so that more people will be interested in visiting the Jatiluwih Tabanan tourist attraction. They should promote the events they hold more so that more people will be interested in visiting. They should also provide attractive destinations and adequate facilities so that many individuals will make the Jatiluwih tourist destination their main destination when planning their future travels.